FORMATION PECULIARITIES OF MODERN BUSINESS MODELS OF ADULT EDUCATION INSTITUTIONS - Yuriy Zelenin; Alevtyna Kudinova (Izdevnieciba "Baltija Publishing", 2020)
One of the main factors for successful formation and implementation of strategic goals of a company is the development of a modern innovative business model concept. The business model should focus on creating and maintaining value of its own product or service, as well as company as a whole. In this publication author studies process of forming a business model for adult education institutions as independent business units that are closely interconnected with business structures. The relevance of this issue is due to the lack in the scientific economic literature of comprehensive studies of business models of adult education institutions. In order to find and select most optimal business model for such organizations, author analyzes modern business models in works of famous scientists and concludes that at the moment in the scientific world there is no single approach to the definition of the essence of the "business model" concept. Based on the analysis of existing business models, author finds out that the main feature of interpretation of "business model" concept in the research of various scientists is a structuring of the main company functional elements aimed at creating value for all stakeholders. Each of the studied theories can be applied to the development of a business model for an adult education institution. Definition analysis of "business model" concept allowed author to single out his own definition of the business model of an adult education institution as a set of interrelated and mutually agreed structural elements of organization's internal and external environment aimed at effective implementation of a continuous qualitative educational process in order to create value for all stakeholders. A promising direction for further research is the development of methodological and organizational support for formation of a business model for an adult education institution.